Exploring the Formation of a Disjunctive Pattern between Eastern Asia and North America Based on Fossil Evidence from Thuja (Cupressaceae) - Cui, Yi-Ming; Sun, Bin; Wang, Hai-Feng; Ferguson, David Kay; Wang, Yu-Fei; Li, Cheng-Sen; Yang, Jian; Ma, Qing-Wen (PLOS ONE, 2015)
Thuja, a genus of Cupressaceae comprising five extant species, presently occurs in both East Asia (3 species) and North America (2 species) and has a long fossil record from Paleocene to Pleistocene in the Northern Hemisphere. Two distinct hypotheses have been proposed to account for the origin and present distribution of this genus. Here we recognize and describe T. sutchuenensis Franch., a new fossil Thuja from the late Pliocene sediments of Zhangcun, Shanxi, North China, based on detailed comparisons with all living species and other fossil ones, integrate the global fossil records of this genus plotted in a set of paleomaps from different time intervals, which show that Thuja probably first appeared at high latitudes of North America in or before the Paleocene. This genus reached Greenland in the Paleocene, then arrived in eastern Asia in the Miocene via the land connection between East Asia and western North America. In the late Pliocene, it migrated into the interior of China. With the Quaternary cooling and drying, Thuja gradually retreated southwards to form today's disjunctive distribution between East Asia and North America.